2021
DOI: 10.3390/nu13041115
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pro-, Pre-, and Synbiotics on Muscle Wasting, a Systematic Review—Gut Permeability as Potential Treatment Target

Abstract: Muscle wasting is a frequently observed, inflammation-driven condition in aging and disease, known as sarcopenia and cachexia. Current treatment strategies target the muscle directly and are often not able to reverse the process. Because a reduced gut function is related to systemic inflammation, this might be an indirect target to ameliorate muscle wasting, by administering pro-, pre-, and synbiotics. Therefore, this review aimed to study the potential of pro-, pre-, and synbiotics to treat muscle wasting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 67 publications
0
25
0
3
Order By: Relevance
“…A recent study revealed that the use of Lactobacillus species could improve the intestinal microbiota and reduce gut permeability [23]. According to Ohland and MacNaughton [24], probiotics improved the intestinal barrier function by increasing the production of mucus, secretory IgA and antimicrobial peptides, and increased tight junction integrity of epithelial cells and competitive adherence for pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that the use of Lactobacillus species could improve the intestinal microbiota and reduce gut permeability [23]. According to Ohland and MacNaughton [24], probiotics improved the intestinal barrier function by increasing the production of mucus, secretory IgA and antimicrobial peptides, and increased tight junction integrity of epithelial cells and competitive adherence for pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal disturbance is one of the major factors contributing to the loss of weight mass and muscle wasting. 1,28 A recent study performed in cachectic rats showed the significantly reduced weight of the caecal and stomach content, and accelerated gastric emptying. 1 This study corroborates our finding that the weight of intestine and average faeces was decreased during PQ exposure while intestinal blockage of MyD88 rescued the loss.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotics such as L. gasseri and L. reuteri have been shown to have a positive effect in mice with cachexia, by decreasing muscle atrophy, inflammation and by increasing intestinal health as well as survival [ [359] , [360] , [361] ]. Upon administration of these probiotics, the level of Lactobacillus spp.…”
Section: Dietary Interventions That Act On Body Weight and That Shape...mentioning
confidence: 99%